2005
DOI: 10.1007/s10540-005-2885-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Activation of Thyroid Hormone and Energy Expenditure

Abstract: The mechanisms by which thyroid hormone accelerates energy expenditure are poorly understood. In the brown adipose tissue (BAT), activation of thyroid hormone by type 2 iodothyronine deiodinase (D2) has been known to play a role in adaptive energy expenditure during cold exposure in human newborns and other small mammals. Although BAT is not present in significant amounts in normal adult humans, recent studies have found substantial amounts of D2 in skeletal muscle, a metabolically relevant tissue in humans. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 98 publications
1
103
1
4
Order By: Relevance
“…As such, inhibition of TRH secretion in HS014-infused rats could conceivably contribute to increased adiposity even if circulating thyroid hormone concentrations are unaltered. Additionally, alterations in local tissue conversion of T4 to the more active T3 and the less active reverse T3 by deiodinase enzymes -which are regulated not only by thyroid hormone concentrations but also by sympathetic activity (Bianco et al, 2005) -could also contribute to reduced thyroid function and therefore reduced fuel oxidation in tissues even in the absence of changes in thyroid hormone levels. In keeping with this, we have shown that both NPY and HS014 inhibited protein or mRNA levels of brown adipose tissue UCP-3 (this study) and UCP-1 (Baran et al, 2002), both proteins undergoing major regulation by sympathetic activity and thyroid hormones (Lanni et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As such, inhibition of TRH secretion in HS014-infused rats could conceivably contribute to increased adiposity even if circulating thyroid hormone concentrations are unaltered. Additionally, alterations in local tissue conversion of T4 to the more active T3 and the less active reverse T3 by deiodinase enzymes -which are regulated not only by thyroid hormone concentrations but also by sympathetic activity (Bianco et al, 2005) -could also contribute to reduced thyroid function and therefore reduced fuel oxidation in tissues even in the absence of changes in thyroid hormone levels. In keeping with this, we have shown that both NPY and HS014 inhibited protein or mRNA levels of brown adipose tissue UCP-3 (this study) and UCP-1 (Baran et al, 2002), both proteins undergoing major regulation by sympathetic activity and thyroid hormones (Lanni et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…All major metabolically relevant organs and tissues (e.g., brain, adipose tissue, liver, and skeletal muscle) are targeted by thyroid hormone. In most tissues, thyroid hormone activates multiple metabolic pathways, leading to a faster ATP turnover (ATP breakdown and synthesis) and accelerated oxygen consumption (588,589). Energy transfer is an inherently thermodynamically inefficient process; that is, heat is an obligatory byproduct when energy is transferred (i) from the oxidation of substrates into ATP and (ii) from ATP into biological work.…”
Section: [J3] Intermediary Metabolism and Energy Homeostasismentioning
confidence: 99%
“…This activation reaction is catalyzed by types 1 and 2 deiodinases (D1 and D2) in peripheral tissues. Both T4 and T3 may also be inactivated by inner ring deiodination to 3,3',5-triiodothyronine (rT3) and 3,3'-diiodothyronine (T2) predominantly by type 3 deiodinase (D3), and to a lesser extent by D1 (16). Deiodination is the most important pathway of thyroid hormone metabolism not only in quantitative terms, but also because it accounts for most of the circulating T3 (~ 80%) in humans (17).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Although thyroid hormones may exert their effects on a number of intracellular loci (16), their actions on target tissues are predominantly mediated by specific nuclear receptors (TRs) able to bind to regulatory regions of target genes modifying their expression (19). Two separate genes, TRa and TRb, encode thyroid hormone receptors (TRs).…”
Section: Thyroid Hormonesmentioning
confidence: 99%